The Effect of Current Ratio, Return on Assets, Net Profit Margin, and Return on Equity on Firm Value with Earnings per Share as a Moderating Variable in Consumer Non-Cyclicals Sector Companies Listed on the Indonesia Stock Exchange - Mega Rizki Hasanawati; Dedi Hariyanto; Heni Safitri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of the Current Ratio (CR), Return on Assets (ROA), Net Profit Margin (NPM), and Return on Equity (ROE) on firm value, proxied by Price to Book Value (PBV), and investigates the moderating role of Earnings per Share (EPS) in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange. The study is motivated by the observation that firms in defensive sectors do not consistently experience higher market valuation, indicating that financial performance indicators may be interpreted selectively by investors. A quantitative associative approach was employed using secondary data obtained through documentation of audited annual financial statements and market data for the 2021–2023 period. The sample was selected using purposive sampling, resulting in 84 companies with 252 firm-year observations. Data were analyzed using classical assumption tests and Moderated Regression Analysis (MRA). The results show that CR and ROA have a negative and significant effect on PBV, while ROE has a positive and significant effect; NPM does not exhibit a significant effect. Furthermore, EPS has a significant direct effect on firm value and moderates the relationships between ROA and PBV as well as ROE and PBV, but does not moderate the effects of CR and NPM on PBV. These findings indicate that firm valuation in the consumer non-cyclicals sector is more sensitive to specific profitability indicators and earnings per share conditions than to liquidity and sales margin measures. Future studies are encouraged to include control variables such as firm size, leverage, and growth to enhance model robustness.